Patients Presenting with Acute Hand and Wrist Injuries at Tertiary Care Center: A Descriptive Cross-sectional Study - Shrestha, Niresh; Batajoo, Santosh; Pandey, Nitesh Raj; Regmi, Subhash; Jaiswal, Sweta; Shrestha, Om Prasad (Nepal Orthopaedic Association Journal, 2024)
Background: Acute hand and wrist injuries are often neglected and result in poor outcomes. Newer studies have suggested that the patterns of these injuries have changed due to changes in the mechanism of injury. This study aims to find out the prevalence of acute hand and wrist injuries in patients presenting to the emergency department of a tertiary care center. Methodology: This was a descriptive cross-sectional study conducted involving patients presented with acute hand and wrist injuries between January 1, 2023, and December 31, 2023. Patients who presented late (>1 week) and those who received treatment at other centers were excluded from the study. The following data were recorded in an electronic proforma: age, gender, mechanism of injury, hand dominance, location of injury (hand, wrist, or both), pattern of injury (blunt, cut, or crush), and associated injuries. Results: A total of 1246 patients visited the emergency department with orthopedic issues. Out of 1246 patients, 153 (12.27%) had acute hand and wrist injuries. The mean age of the patients was 27.16 ± 14.14 years, 129 (82.69%) were male and 24 (18.60%) were female. The mechanism of injury was road traffic accidents in 54 (35.30%), occupational hazard in 46 (30.07%), falls in 29 (18.95%), and others in 24 (15.68%). The type of injury was crush in 51 (33.33%), cut in 43 (28.10%), blunt in 38 (24.83%), and avulsion in 21 (13.72%) patients. The associated injuries were present in 48 (31.37%) patients. Conclusion: The prevalence of hand and wrist injuries was 12.27% among patients with orthopedic trauma. RTA was the most common mechanism of injury, followed by occupational hazards. Crush injuries were the most common injury pattern, followed by cut injuries. The findings were similar to those reported in studies conducted in similar settings.